COMPETITIVENESS OF PADDY RICE FARMING TO INCREASE FARMERS' INCOME IN SERANG REGENCY - Dian Anggraeini; Aliudin Aliudin; Eka Laelah (AGRIBUSINESS JOURNAL, 2022)
Rice is the staple food of most Indonesians, therefore rice as a strategic commodity that must be maintained and regulated by the government. This study aims to: 1) analyze the competitiveness of paddy rice farming in Serang Regency, 2) analyze the impact of government policies on the competitiveness of paddy rice farming in Serang Regency, 3) analyze the impact of government policies on the welfare of paddy rice farmers in Serang Regency. This study used primary (obtained from respondents related to this study both through observations, interviews, and questionnaires) and secondary (obtained from relevant agencies and scientific publications). The study was conducted in Serang Regency, the number of respondents in this study was 84 people consisting of: Pontang District as many as 27 respondents, Tirtayasa district as many as 29 respondents, and Tanara District as many as 28 respondents. The method in this study is quantitative, the analysis tool used is the Policy Analysis Matrix (PAM). The Policy Analysis Matrix (PAM) is used to analyze the competitiveness of paddy rice farming, analyze the impact of government policies on paddy rice farming, and analyze the impact of government policies on the welfare of paddy rice farmers in Serang Regency. The results showed that the competitiveness of paddy rice farming is financially (private) and economically (social), has competitiveness comparatively and competitively with PCR and DRC values of paddy rice farming, namely 0.16 and 0.17, respectively. The impact of government policies provides incentives to develop paddy rice farming in Serang Regency reflected by the NPCI value = 0.62; NPCO = 1.015; EPC = 1.03 and SRP = 0.03 which are all positive. This means that the government has effectively protected rice farming in Serang Regency.